Solve the following inequality: 5x + 3 < 6x + 2

Answers

Answer 1
Answer:


Related Questions

Simplify;4t-2k+5k-t?Help
You cannot bisect an angle using paper folding constructions True or False
Pick a product that might be packaged in the shape of a rectangular prism.Surface Area: S.A.=2lw+2wh+2lh Volume: V=lwh Choose an appropriate length, width, and height for your package so that it can fit the product you are shipping. Using these dimensions, what is the ratio of surface area to volume?
A hardcover book sells for 24$ at the bookmart. Ben pays 25.02 for the book. What is the sales tax rate?
The diameter of the base of the cone measures 8 units.The height measures 6 units. What is the volume of the cone? A)240 cubic units B)321 cubic units C)48X cubic units D)647 cubic units

.Find the proceeds for the simple discount note.
Face value $4,530, discount rate 7.2%, time 125 days


$113.25

$111.70

$4,416.75

$4,418.30

Answers

4530-(4530*0.072*125/360)
=4416.75

Given the tables for f & g below, find the following: x f ( x ) g ( x ) 0 9 7 1 4 8 2 3 6 3 5 1 4 7 5 5 1 2 6 6 0 7 0 4 8 2 9 9 8 3 Average rate of change of g for x on the interval [3 , 7 ] = 9 Incorrect Average rate of change of f for x on the interval [3 , 7 ] = Incorrect f ( g ( 4 ) ) = Incorrect g ( f ( 3 ) ) = Incorrect

Answers

\n(i)\n\text{We know that the average rate of change of a function f(x) on inerval [a,b] is}\n\nf_(avg)=(f(b)-f(a))/(b-a)\n\n\text{so using this the average rate of chang of g for x on interval }[3,7] \text{ is}\n\ng_(avg)=(g(7)-g(3))/(7-3)\n\n=(4-1)/(4)\n\n=(3)/(4)\n\n\text{so average rate of change of g on interval [3,7] is }(3)/(4)

\n(ii)\n  \text{Average rate of chang of f for x on interval }[3,7] \text{ is}\n\nf_(avg)=(f(7)-f(3))/(7-3)\n\n=(0-5)/(4)\n\n=(-5)/(4)\n\n\text{so average rate of change of g on interval [3,7] is }(-5)/(4)

\n(iii)\n\text{Since g(4)=5, so we have}\n\nf(g(4))=f(5)\n\n\text{since the value of f is 1 at x=5. so }\n\nf(g(4))=f(5)=1\n\n\text{hence we have, }f(g(4))=1

\n(iv)\n\text{Since f(3)=5, so we have}\n\ng(f(3))=g(5)\n\n\text{since the value of g is 2 at x=5. so }\n\ng(f(3))=g(5)=2\n\n\text{hence we have, }g(f(3))=2

Bryan’s monthly electric bill is determined by adding a flat administration fee to the product of the number of kilowatt hours of electricity used and the cost per kilowatt hour. When he uses 1,100 kilowatt hours of electricity, his bill is $113. When he uses 1,500 kilowatt hours of electricity, his bill is $153. What is the monthly administration fee?

Answers

We will form the equations for this problem:
(1) 1100*y + z = 113
(2) 1500*y + z = 153
z = ? Monthly administration fee is notated with z, and that is the this problem's question.
Number of kilowatt hours of electricity used are numbers 1100 and 1500 respectively.
Cost per kilowatt hour is notated with y, but its value is not asked in this math problem, but we can calculate it anyway.
The problem becomes two equations with two unknowns, it is a system, and can be solved with method of replacement:
(1) 1100*y + z = 113
(2) 1500*y + z = 153
----------------------------
(1) z = 113 - 1100*y [insert value of z (right side) into (2) equation instead of z]:
(2) 1500*y + (113 - 1100*y) = 153
-------------------------------------------------
(1) z = 113 - 1100*y
(2) 1500*y + 113 - 1100*y = 153
------------------------------------------------
(1) z = 113 - 1100*y
(2) 400*y + 113 = 153
------------------------------------------------
(1) z = 113 - 1100*y
(2) 400*y = 153 - 113
------------------------------------------------
(1) z = 113 - 1100*y
(2) 400*y = 40
------------------------------------------------
(1) z = 113 - 1100*y
(2) y = 40/400
------------------------------------------------
(1) z = 113 - 1100*y
(2) y = 1/10
------------------------------------------------
if we insert the obtained value of y into (1) equation, we get the value of z:
(1) z = 113 - 1100*(1/10)
(1) z = 113 - 110
(1) z = 3 dollars is the monthly fee.

Answer:

3

Step-by-step explanation:

correct on ed (:

please help :) Which sentence is true? A. 9.46 times 10 to the 12 power > 4.0 times 10 to the 13 power B. 9.46 times 10 to the 12 power < 4.0 times 10 to the 13 power

Answers

Answer:

B

Step-by-step explanation:

The problem is simple because they use powers of 10. When something is multiplied by a power of ten, it is essentially moving the decimal point over for every power.

9.46x10^12= 9460000000000

4.0x10^13= 40000000000000

Although 4 itself is less than 9.46, since is is being multiplied by 10^13, it will be one decimal place bigger.

What does the line x= 2 look like?

Answers

X = 2 means for whatever y value you select the x value will be 2. So if you graph a couple of coordinates it becomes quickly evident that x = 2 is a vertical line that crosses the x axis at 2.
x = 2

This would show a vertical line crossing the x axis at 2. 

Since y = 0, there is no y intercept, which means it does not cross the y axis. 


How do you write fourteen and seven tenths squared in all three forms?

Answers

The 3 forms of expressing fourteen and seven tenths squared are;

(14⁷/₁₀)²; (147/10)²; (14.7)²

How to express fractions in decimal form

We want to express 14 and 7/10 all squared in all three forms.

The first form is in mixed fraction which is;

(14⁷/₁₀)²

Second form is in improper fraction form which is;

(147/10)²

Third form is in decimal form which is; (14.7)²

Read more about fractions to decimal form at; brainly.com/question/293712

14.7 squared
14 7/10 squared
14.7 × 14.7